MODERN RESEARCH IN THE FIELD OF FOREIGN LANGUAGES TEACHING METHODS, LINGUISTICS, PEDAGOGY (Konferensiyalar | Conferences, 2024)
The article is an analysis of current areas of methodological research in the field of methods of teaching English as a foreign language. The main feature of modern methodology is attention to problem solving, related to the language acquisition of each student. Practice has convincingly proven that in the educational process there is no minor, unimportant components. Hence, it is necessary to optimize not individual, but all links of the educational process, which should ultimately lead to the creation of an adequate psychophysiological structure of training, taking into account various social, sociolinguistic, psychological and other factors.